Pengaruh Inflasi, Kurs, Ekspor, Impor dan Investasi terhadap Pertumbuhan Ekonomi Indonesia Periode 2010-2023 - Watoni, M. (Universitas Batanghari Jambi, 2024)
Economic Growth is an important phenomenon for a nation, the problem of economic growth can be viewed as a long-term problem. Economic growth is the goal of the nation so that it can also increase National Development which can improve the quality of Indonesian people and society which is carried out sustainably based on national capabilities. Economic growth is an important indicator in measuring the level of community welfare. Economic growth as a measure of the economic activity of the community in generating additional income in a certain period. The purpose of this study is to test Inflation, Exchange Rates and Import Export Values and Investment on Indonesia's Economic Growth in the Period 2010-2022 simultaneously and partially. This research technique uses a quantitative descriptive approach, and the Multiple Linear Regression analysis tool is useful in determining the relationship between independent variables and dependent variables. And SPSS version 25 is a tool used to analyze research data. The tests carried out are the F test for the hypothesis, the t test for the hypothesis, and the coefficient of determination (R2). Judging from its geographical location, Indonesia is located between two continents (the Australian Continent and the Asian Continent) and between two oceans (the Indian and Pacific). Indonesia is one of the largest archipelagic countries, in addition, Indonesia's land area consists of tropical rainforests, although currently Indonesia's forest area has decreased, the total area is 1,904,569 km2, with a comparison of land area of 1,811,569 km2 and water area of 93,000 km2. Based on the results of this study, simultaneously based on the F test, it is known that Inflation, Exchange Rates and Import Export Values and Investment have a significant effect on Indonesia's Economic Growth. Because the calculated F value is greater than the F table (5.217> 3.69). And partially based on the t-test, exports, imports and investment have a significant effect on economic growth because the calculated t is greater than the t table. The R Square value of 0.762 explains that the X variables exports, imports and investment affect the Y variable (economic growth) by 0.599 or 76.20%.